THЕОRЕTIСАL FОUNDАTIОNS ОF TЕАСHING ЕNGLISH TЕRMINОLОGY IN NОN-PHILОLОGIСАL HIGHЕR ЕDUСАTIОNАL INSTITUTIОNS. (Scientific journal of the Fergana State University, 2024)
In today's rapidly developing era, English is the main communication language of the world. The influence of the English language on the Uzbek language is very large and it can be seen mainly in various fields of science, industry, technology and social life. In many cases, we try to find the equivalent of terms and terms in English based on the internal capabilities of the Uzbek language. However, there are terms for international terms, terms or international words that are used in the same form in English and Uzbek without any changes. In this article, the importance of terminology and its importance in every field have been studied with comprehensive opinions, views and opinions given by scientists. Also, the theoretical bases, difficulties and important aspects of teaching in non-philological higher educational institutions by connecting the terminology of the English language to the terms of the field are highlighted.